Report of the Task Force Measures for Operationalising Open Access in the Power Sector - Planning Commission (Planning Commission, 2009)
The Electricity Act 2003 mandates non-discriminatory open access to transmission and distribution networks that would allow competing producers and suppliers to sell electricity directly to bulk consumers. The National Electricity Policy 2005 and Tariff Policy 2006 have reinforced these provisions by specifying the principles for determination of surcharge on open access with a view to enabling competition. Over the last two decades, most of the developed countries have introduced such competition and some have gone right down to the level of household consumers in providing a choice of suppliers. Besides efficiency improvements and cost reduction introduction of open access would create a market that would help increase investment because the present market structure compels producers to sell to monopoly utilities alone.
Planning Commission Government of India
Planning Commission Government of India